2016
DOI: 10.1364/oe.24.013542
|View full text |Cite
|
Sign up to set email alerts
|

New vibration-assisted magnetic abrasive polishing (VAMAP) method for microstructured surface finishing

Abstract: In order to polish microstructured surface without deteriorating its profile, we propose a new vibration-assisted magnetic abrasive polishing (VAMAP) method. In this method, magnetic force guarantees that the magnetic abrasives can well contact the microstructured surface and access the corners of microstructures while vibration produces a relative movement between microstructures and magnetic abrasives. As the vibration direction is parallel to the microstructures, the profile of the microstructures will not … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(6 citation statements)
references
References 23 publications
0
6
0
Order By: Relevance
“…They applied this method to the finishing of stainless steel and found that the vibration-assisted deburring time was reduced by 40% compared with no vibration, and the initial surface of 2.5 µm Ry pre-polish was improved to 0.45 µm Ry after four passes of polishing. Further, Guo et al [245] proposed a vibration-assisted magnetic abrasive polishing (VAMAP) method, which could polish micro-featured surfaces. The surface roughness Ra increased from 166.9 nm to 25.4 nm and from 2.23 µm to 0.32 µm when the rectangular microstructure and the miniature V-grooves were polished, respectively.…”
Section: Magnetic Abrasive Finishingmentioning
confidence: 99%
“…They applied this method to the finishing of stainless steel and found that the vibration-assisted deburring time was reduced by 40% compared with no vibration, and the initial surface of 2.5 µm Ry pre-polish was improved to 0.45 µm Ry after four passes of polishing. Further, Guo et al [245] proposed a vibration-assisted magnetic abrasive polishing (VAMAP) method, which could polish micro-featured surfaces. The surface roughness Ra increased from 166.9 nm to 25.4 nm and from 2.23 µm to 0.32 µm when the rectangular microstructure and the miniature V-grooves were polished, respectively.…”
Section: Magnetic Abrasive Finishingmentioning
confidence: 99%
“…were used to analyses the findings. Some Miscellaneous methodologies used such as finite element method, finite volume method and finite difference method to find out new models [2,3,7,11,13,24,30]. So we concluded that most of the researcher have focused on material removal along with some researchers have coted some material with magnetic abrasive particle as wire magnetic and induction free abrasive wire sawing (MIFAWS) is one of the method by which Chunyan Yao et al have prepared magnetic abrasive particle layer on the wire surface and then thickness was calculated for to find out how much magnetic Process was analyzed by MATLAB and results are discussed in detail for developing new areas of research [1].…”
Section: Literature Reviewmentioning
confidence: 99%
“…So we concluded that most of the researcher have focused on material removal along with some researchers have coted some material with magnetic abrasive particle as wire magnetic and induction free abrasive wire sawing (MIFAWS) is one of the method by which Chunyan Yao et al have prepared magnetic abrasive particle layer on the wire surface and then thickness was calculated for to find out how much magnetic Process was analyzed by MATLAB and results are discussed in detail for developing new areas of research [1]. The model used for machining is thermo-physical [24,25,26], electro-mechanical and thermo-electrical [27,28,29,30]. EDM and WEDM process is used for some complicated and tough to machine work pieces and for these machines the numerical model is created to analyses the process parameters for optimization [4,6,14,17], and for semi observational data [19,20].…”
Section: Literature Reviewmentioning
confidence: 99%
“…At present, the main way to improve the surface quality after SPDT is polishing [12]. Guo et al proposed a new vibration-assisted magnetic abrasive polishing (VAMAP) method, the quality of the V-groove surfaces after polishing is effectively improved, and the initial tool marks and burrs are removed, but this method is not suitable for magnetic workpiece [13,14].…”
Section: Introductionmentioning
confidence: 99%